Introduction to Dynamics - Ghosh, Amitabha (Springer Singapore, 2018)
This book is intended to serve as a text on dynamics for undergraduate studenst of engineering. The book provides in-depth discussions of the fundamentals of Newtonian mechanics, more commonly known as dynamics. Drawing on the author's extensive experience in teaching the subject of dynamics at two Indian Institutes of Technology (IITs) and the Indian Institute of Engineering Science and Technology (IIEST), the book contains 498 line diagrams, 123 worked-out examples and 222 exercise problems. The answers to select exercise problems are provided at the end of the book. A wealth of detailed illustrations make the book ideally suited for both self self-study and classroom use at both introductory and secondary levels. Thus the book offers a valuable resource for both students and teachers of dynamics, addressing the main topics covered in core level courses on 'Dynamics' for students of civil, mechanical and aerospace engineering across the globe.